Responses of economic and anatomical leaf traits to soil fertility factors in eight coexisting broadleaf species in temperate forests - Jin, Mingyue; Jin, Guangze; Guo, Qingxi; Liu, Zhili (Frontiers in Forests and Global Change, 2023)
The multidimensionality of leaf traits allows plants to have diverse survival strategies to adapt to complex living environments. Whether the anatomical traits of leaves are associated with leaf economic traits and which group of traits are more strongly correlated with soil fertility factors remains unclear. We measured four leaf economic traits, four anatomical traits, and five soil fertility factors of 8 coexisting broadleaf species distributed in mixed broadleaved-Korean pine (Pinus koraiensis) forests located in Northeast China. Results show a strong interdependence between economic and anatomical traits (p < 0.05). The range of variation between economic and anatomical traits were almost equal, but the causes of variation were different. Specific leaf area was positively correlated with the abaxial epidermis, negatively correlated with the ratio of spongy tissue to leaf thickness (ST/LT), and not correlated with adaxial epidermis. Leaf dry matter content was negatively correlated with the abaxial epidermis and adaxial epidermis, positively correlated with ST/LT. Specific leaf area, palisade tissue and ST/LT showed stronger correlation with soil fertility factors than other traits. Soil fertility factors dominating trait variation were dependent upon the trait. Our results suggest anatomical traits can be considered in economic trait dimension. The coupled relationship between anatomical and economic traits is potentially a cost-effective adaptation strategy for species to improve efficiency in resource utilization. Our results provide evidence for the complex soil-trait relationship and suggest that future studies should emphasize the role of anatomic traits in predicting soil fertility changes.